Accuracy assessment of a model-based human motion measurement system, a pilot study. (15th December 2006) - Oudenhuijzen, A.J.K.; Seitz, T.; Bubb, H.
The goal of this pilot study was to assess the accuracy of a model-based human motion measuring system. We compared motion capture data from a model-based system with those from a marker-based system. A simple reach task involving the left shoulder, upper arm and lower arm was used for the comparison in two subjects. The results revealed various errors in the model-based system. The modelled movements for the upper arm and lower arm laid within the standard error for most of the motion sequences of the marker-based system. The modelled end positions deviated from the actual motion sequence in Y and Z direction with 17 and 23%, respectively. The shoulder movement algorithm, in the model-based system, could not be used. Hence, the shoulder was assumed not to move in the marker-based system. However, despite these errors, there are advantages in using the model-based system. Preparation time for subjects decreases since marker placement is not needed in the model-based system. Hence, model-based motion capturing shows potential to enhance human modelling towards dynamics.